Short-term effects of repeated-sprint training on vertical jump ability and aerobic fitness in collegiate volleyball players during pre-season - Gantois, P.; Batista, G. R.; Fortes, L. S.; Mortatti, A. L.; Dantas, M.; da Silva Machado, D. G.; de Araújo Tinoco Cabral, B. G. (International Journal of Exercise Science, 2022)
The aim of this study was to assess the effect of repeated-sprint training (RST) on vertical jump ability and aerobic power in college volleyball players. Nineteen male volleyball players, aged between 18-24 years, were randomized into the RST group (RST; n = 10) and control group (CG; n = 9). The RST included 2-3 sets of 6x30m all-out sprints, twice per week, in addition to the regular training routine. The control group performed only the regular volleyball training sessions (i.e. mainly of technical-tactical drills). All players performed a maximal graded treadmill test, vertical countermovement jump (CMJ), and repeated-vertical jump ability (RVJA) test before and after 6-weeks of the training program. The following variables were determined from the RVJA: peak (RVJApeak), average (RVJAmean), and rate of decrement (RVJADec). A two-way ANOVA with repeated measures showed an interaction effect on CMJ (F(1,17) = 6.92; p = 0.018; ?2 = 0.289), RVJApeak (F(1,17) = 4.92; p = 0.040; ?2 = 0.225), maximal oxygen uptake (F(1,17) = 9.29; p = 0.007; ?2 = 0.353) and maximal speed attained in the treadmill test (F(1,17) = 8.66; p = 0.009; ?2 = 0.337), with significant improvements only on the RST group. In conclusion, RST, twice per week, improved RVJA and aerobic power in comparison to regular skill-based volleyball training.